Spatiotemporal evolution and driving forces of ecosystem service value and ecological risk in the Ulan Buh Desert - Liu, Huan; Wang, Ruizhen; Sun, Haoyu; Cao, Weijia; Song, Jie; Zhang, Xuefeng; Wen, Lu; Zhuo, Yi; Wang, Lixin; Liu, Tiejun (Frontiers in Environmental Science, 2023)
A comprehensive assessment of the spatiotemporal evolution laws and driving factors of ecosystem service value (ESV) and landscape ecological risk (ecological risk index, ERI) can effectively link human well-being and ecosystem security, thus providing new ideas for the construction of ecological security patterns. Based on gridded multitemporal land use data (1990, 2000, 2010, and 2018), the spatiotemporal evolution of ESV and ERI in the Ulan Buh Desert was evaluated. The driving forces of ESV and ERI were quantitatively evaluated by the Geodetector model. The results showed that (1) from 1990 to 2018, the total ESV in the Ulan Buh Desert increased from 7.00×108 yuan to 11.09×108 yuan. The low-ESV areas accounted for about 72.28% of the study area. The high-ESV and medium-high-ESV areas were mainly distributed along the Yellow River and the northeastern region. (2) During the study period, the ecological risk of the Ulan Buh Desert was generally reduced; only the ecological risk of the northeastern region improved significantly, and the high-risk areas were mainly distributed in the sand dunes located in the middle of the desert. (3) There was a certain negative correlation between ESV and ERI in the study area, and the main relationship was low value-high risk. (4) The driving force analysis results showed that natural factors and human impact factors jointly affected the spatiotemporal differentiation of ESV and ERI in the Ulan Buh Desert. Among the influencing factors, the interaction between the distance to a highway and annual precipitation had the strongest impact. The implementation of relevant policies in the study area should be guided by ESV and ERI, and the protection and restoration of various ecosystems in the study area must be strengthened.